Nuclear Involvement in the Appearance of a Chloroplast-Encoded 32,000 Dalton Thylakoid Membrane Polypeptide Integral to the Photosystem II Complex - Leto, Kenneth J. (1982)
The genetic locus for the high chlorophyll fluorescent photosystem II-deficient maize mutant hcf(*)-3 has been definitively located to the nuclear genome. Fluorography of lamellar polypeptides labeled with [(35)S]methionine in vivo revealed the specific loss of a heavily labeled 32,000 dalton thylakoid membrane polypeptide as well as its chloroplast encoded precursor species at 34,000 daltons. Examination of freeze-fractured mesophyll and bundle sheath thylakoids from hcf(*)-3 revealed that both plastid types lacked the large EFs particles believed to consist of the photosystem II reaction center-core complex and associated light harvesting chlorophyll-proteins. The present evidence suggests that the synthesis or turnover/integration of the chloroplast-encoded 34,000 to 32,000 dalton polypeptide is under nuclear control, and that these polyipeptides are integral components of photosystem II which may be required for the assembly or structural stabilization of newly formed photosystem II reaction centers in both mesophyll and bundle sheath chloroplasts.